Immune and Nervous Systems Interaction in Endocrine Disruptors Toxicity: The Case of Atrazine - Galbiati, Valentina; Buoso, Erica; d'Emmanuele di Villa Bianca, Roberta; Paola, Rosanna Di; Morroni, Fabiana; Nocentini, Giuseppe; Racchi, Marco; Viviani, Barbara; Corsini, Emanuela (Frontiers in Toxicology, 2021)
Endocrine disruptors (ED) are natural and anthropogenic chemicals that can interfere with hormonal systems at different levels. As such, ED-induced alterations in hormone functions have been implicated in many diseases and pathological conditions, including adverse developmental, reproductive, neurological, cardiovascular, and immunological effects in mammals. The fact that ED may compete with several endogenous hormones for multiple receptors and pathways is not always fully considered. This results in a complex response that depends on the cellular context in terms of receptors and interacting proteins and, thus, may differ between tissues and circumstances. Microglia, neurons, and other immune cells are potential targets and still underappreciated actors in endocrine disruption. Due to the large scale of this topic, this review is not intended to provide a comprehensive review nor a systematic review of chemicals identified as endocrine disruptors. It focuses on the immune-neuro-endocrine network in ED toxicity and research gaps, using atrazine as an example to highlight this complexity and the interrelationship between the immune, endocrine, and nervous systems, and ED.